2012
DOI: 10.1309/ajcp6j2oefoytrfd
|View full text |Cite
|
Sign up to set email alerts
|

HPV Testing Is an Efficient Management Choice for Women With Inadequate Liquid-Based Cytology in Cervical Cancer Screening

Abstract: This study compares colposcopy referrals of 2 management strategies: oncogenic human papillomavirus (HPV)-DNA testing (Hybrid Capture 2 assay, Qiagen, Germantown, MD) and repeat cytology. In the New Technology in Cervical Cancer Trial, 22,708 subjects were randomly assigned to undergo both HPV and liquid-based cytologic testing. Women aged 35 to 60 years old with unsatisfactory cytologic findings were directly referred for colposcopy if the HPV test result was positive, and were referred for repeat cytologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…However, in NTCC study the most frequently represented category was ASCUS, but with a value below the limits set by the GISCi guidelines (< 5%) [5], while in the present study the authors observed that the most frequently diagnosed category was LSIL (2.3%). Moreover, through the hr-HPV test used as triage of ASCUS category, the present authors showed that 69.9% of women with diagnosis of ASCUS were infected with the hr-HPV, and this value was higher than NTCC study that included the ASCUS+ category (60.6%) [17]. These data confirm that the ASCUS triage using hr-HPV test can help the operators in the management of women aged 25-34 with diagnosis of ASCUS in order to avoid unnecessary colposcopies [18].…”
Section: Discussioncontrasting
confidence: 52%
“…However, in NTCC study the most frequently represented category was ASCUS, but with a value below the limits set by the GISCi guidelines (< 5%) [5], while in the present study the authors observed that the most frequently diagnosed category was LSIL (2.3%). Moreover, through the hr-HPV test used as triage of ASCUS category, the present authors showed that 69.9% of women with diagnosis of ASCUS were infected with the hr-HPV, and this value was higher than NTCC study that included the ASCUS+ category (60.6%) [17]. These data confirm that the ASCUS triage using hr-HPV test can help the operators in the management of women aged 25-34 with diagnosis of ASCUS in order to avoid unnecessary colposcopies [18].…”
Section: Discussioncontrasting
confidence: 52%
“…29 Human papilloma virus (HPV) DNA testing has also been shown to be a better approach than repeated Pap tests in resolving unsatisfactory results. 30 HPV DNA testing should be investigated as a potentially patient-centered and clinically effective method of primary cervical cancer screening for transgender men. Use of stand-alone HPV DNA testing for primary cervical cancer screening has been studied in non-transgender women, and has been found to have some advantages, including increased sensitivity with only slightly reduced specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have documented that HPV test results may be positive despite unsatisfactory cytology results and can provide clinically useful follow‐up information . However, those studies were conducted in conjunction with cytology testing, and the study by Rossi et al classified specimens that lacked a transformation zone component as unsatisfactory.…”
Section: The Papanicolaou Test and Cervical Cancer In The United Statesmentioning
confidence: 99%